Variations on the same theme: Environmental objectives of the Water Framework Directive in environmental permitting in the Nordic countries. Issue 2 (28th January 2019) - Kymenvaara, Sara; Baaner, Lasse; Anker, Helle Tegner; Leino, Laura; Belinskij, Antti
Abstract : The Court of Justice of the European Union's (CJEU) interpretations on the normativity of the Water Framework Directive's (WFD) environmental objectives and derogation for new, important activities clarified certain long‐standing discussions on these matters in the Nordic countries. The WFD's legal narrative formally changed from a planning framework for gradual improvement of water quality in the European Union to one of legally binding character for the environmental objectives. This simultaneously increased the interest for the circumstances under which a derogation from the environmental objectives is applicable for certain new activities. Both of these matters are integrally connected to the authorization of activities under national environmental permitting legislation. This article explores how and to what extent the WFD's environmental objectives are given legal effect in national environmental permitting in Sweden, Finland and Denmark. Although the Nordic countries have chosen different approaches when implementing the WFD, they have all largely kept these legal frameworks separate; legislation establishing a system of river basin management planning pursuant to the WFD on the one hand, and environmental permitting legislation on the other. The article points out certain crucial questions on the reconciliation of these legal frameworks and the development of national legislation as triggered by the CJEU case law. Regarding the provisions implementing the possibility to derogate for new and important activities, the article discusses certain lacking and flawed legal linkages between river basin management planning and environmental permitting in the three countries.